2017
DOI: 10.1103/physrevb.96.075413
|View full text |Cite
|
Sign up to set email alerts
|

Tunable narrow-band near-field thermal emitters based on resonant metamaterials

Abstract: In the near field, Planck's law of blackbody radiation breaks down, and radiative heat transfer can be enhanced by orders of magnitude when surface polaritons are supported by interacting materials. However, such thermal radiation enhancement is strongly material-dependent thus difficult to control. Here, we propose a new metamaterial-based structure consisted of patterned doped silicon nanorods which exhibits tunable narrow-band thermal emission. Direct numerical simulation based on the Wiener-chaos Expansion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…Multilayer thermal metamaterial designs have also experimentally demonstrated that thermal radiation can be controlled by engineering the optical topological transition [2]. Such advances in thermal radiation control can impact a variety of commercial applications such as coherent infrared sources [5,4,15,16], thermophotovoltaics [9,13,17,18,11], radiative cooling [19,20], temperature sensors, gas sensors [21], nanoscale heat transfer [22,23,24,25] and general thermal management.…”
Section: Introductionmentioning
confidence: 99%
“…Multilayer thermal metamaterial designs have also experimentally demonstrated that thermal radiation can be controlled by engineering the optical topological transition [2]. Such advances in thermal radiation control can impact a variety of commercial applications such as coherent infrared sources [5,4,15,16], thermophotovoltaics [9,13,17,18,11], radiative cooling [19,20], temperature sensors, gas sensors [21], nanoscale heat transfer [22,23,24,25] and general thermal management.…”
Section: Introductionmentioning
confidence: 99%
“…The GNRs are embedded in alumina with two different spacings, 200 and 400 nm. The direct simulation of thermal emission from the GNRs is conducted based on the Wiener‐chaos expansion (WCE) method [ 34,35 ] using the finite‐different time‐domain (FDTD) calculation, where we put a set of dipole source arrays inside the GNRs to mimic the thermally excited current density. The position, intensity and polarization of the dipole sources inside the GNRs are carefully designed such that different sets of dipole sources are orthogonal to each other, which manifests the incoherence nature of thermal sources.…”
Section: Theory Of Mode Hybridization In a Gold Nanorod Arraymentioning
confidence: 99%
“…Second, the emitter-fiber system can be easily fabricated in practice. Here, we experimentally measure the thermal emission spectrum of ITO thin films doped by H 2 gas with different concentrations and compare the measurement results with the direct simulations from the WCE method 9 .…”
Section: Experimental Demonstration Of the Thermal Emission Extrmentioning
confidence: 99%
“…Thermal radiation plays an increasingly important role in many applications such as radiative cooling 1,2 , gas sensing 3 , and thermal management 4,5 . While technology development for the spectral and directional control of thermal radiation becomes more and more sophisticated in recent years [6][7][8][9][10][11][12] , the intensity of the thermal radiation in the far field is still tightly confined by the blackbody radiation limit. To address this challenge, significant efforts have been taken to utilize the near-field thermal radiation where the energy density of electromagnetic waves can be orders of magnitude larger than that in the far field due to the contribution from evanescent waves [13][14][15][16][17][18][19][20][21][22][23] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation